2008
DOI: 10.1016/j.psyneuen.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and nucleus accumbens dopamine in the male Syrian hamster

Abstract: SummaryMost drugs of abuse increase dopamine (DA) in nucleus accumbens (Acb). However, the effects of anabolic androgenic steroids (AAS) on Acb DA have not been examined. We determined the effects of subcutaneous (sc) testosterone (T) on Acb DA in male hamsters. The effects of sc amphetamine were also examined for comparison. In addition, Acb DA was evaluated during intracerebroventricular (ICV) T infusion, designed to mimic T intake during ICV T selfadministration in drug-naïve and drug-preexposed animals. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Testosterone injection into the nucleus accumbens also induced conditioned place preference, and this effect could be blocked by D1 and D2 antagonists (Packard et al, 1997;Schroeder and Packard, 2000). Moreover, this effect was produced only by stimulation of the shell, not the core, of the nucleus accumbens (Frye et al, 2002), but not under all conditions (Triemstra et al, 2008). These findings have been interpreted as evidence for non-genomic stimulation of dopaminergic activity by testosterone (Wood, 2004).…”
Section: Interactions Between Cocaine and Neuroactive Steroid Hormonesmentioning
confidence: 88%
“…Testosterone injection into the nucleus accumbens also induced conditioned place preference, and this effect could be blocked by D1 and D2 antagonists (Packard et al, 1997;Schroeder and Packard, 2000). Moreover, this effect was produced only by stimulation of the shell, not the core, of the nucleus accumbens (Frye et al, 2002), but not under all conditions (Triemstra et al, 2008). These findings have been interpreted as evidence for non-genomic stimulation of dopaminergic activity by testosterone (Wood, 2004).…”
Section: Interactions Between Cocaine and Neuroactive Steroid Hormonesmentioning
confidence: 88%
“…Thiblin et al [171] observed an increase in DA synthesis in response to methandrostenolone, and nandrolone stimulates the DA metabolite 3,4-dihydroxyphenylacetic acid (DOPAC) in cerebral cortex [99]. On the other hand, as measured by in vivo microdialysis with HPLC, testosterone does not appear either to stimulate Acb DA release [177], or to potentiate amphetamine-stimulated DA in Acb [13]. Furthermore, Acb and VTA have few classical androgen receptors [97], suggesting that the reinforcing effects of intra-Acb androgens may be mediated by non-genomic receptors.…”
Section: Dopaminementioning
confidence: 99%
“…Moreover, such effects are blocked by GBR antagonists and potentiated by GBR agonists (Frye, 2007). Thus, both genomic and nongenomic mechanisms of action may contribute to reinforcing effects of testosterone, but the exact pathways remain to be fully clarified (Triemstra et al, 2008).…”
Section: Contrast/regionmentioning
confidence: 99%